Chapter L'apporto delle neuroscienze rappresenta un punto di svolta per la critica letteraria? - MORDENTI, RAUL (Moderna/Comparata, 2022)
Theoretical studies on literature and the methodology of literary criticism have always been a field of high intellectual "porosity" capable of opening up to diverse and novel disciplinary stimuli and expertise. However, this capacity, which is moreover a necessary characteristic of proper research, clashes with the rigidity of the disciplinary structure of the Italian university, based on rigid taxonomies of knowledge. Overcoming this rigidity is now desirable and necessary to release the innovative potential of the so-called frontier fields of study.